Occlusion and Temporomandibular Disorders: A Scoping Review - Laurențiu Pascu; Raul-Samuel Haiduc; Oana Almășan; Daniel-Corneliu Leucuța (Medicina)
Background and Objectives: The occlusal–temporomandibular disorder (TMD) relation is a contentious issue in dentistry to date. This scoping review’s purpose was to map the existing literature on occlusal abnormalities and their potential role in the development and progression of TMD. Materials and Methods: A search in PubMed, Scopus, Cochrane Library, Embase, Lippincott, Medknow, and ClinicalKey was conducted. Articles researching the relationship between TMD and occlusion have been selected. A narrative data synthesis was conducted to chart and summarize the main findings from the included studies. Results: A total of 29 articles were included in this review. These studies confirm that angle class II and angle class III malocclusions, deep bite, and crossbite have a high prevalence of symptoms of TMD, including mandibular deviation, arthritic pain, and tenderness of the muscles. Malocclusion, edentulous spaces, and a reduced vertical dimension of occlusion (VDO) also contribute to the severity of TMD, most prominently in older adults. TMD is also seen with high prevalence in females, with a female-to-male ratio of 2:1 to 20:1, according to studies. Bruxism, premature occlusal contacts, and occlusal interferences also contribute towards symptoms of TMD, in agreement with multiple facets of the disorder. Conclusions: Occlusal abnormalities have a significant association with TMD, but causality cannot be established with most observational studies. This review emphasizes the need for early occlusal examination and intervention to reduce TMD risk.